PENINGKATAN KEMAMPUAN PSIKOMOTORIK ANAK USIA DINI MENGGUNAKAN ALAT PERMAINAN EDUKATIF BERBASIS BUDAYA MANDAR - Asdar, Asdar; Syamsuddin, Syamsuddin; Rahayu, Ayu (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
Childhood is a child's golden age, where all aspects of a child's development grow and develop rapidly. There are several aspects of early childhood development, one of which is the psychomotor aspect. The development of these aspects must be carried out in an integrated manner according to the child's development stage. The psychomotor aspect is part of individual development which is related to physical movement based on the results of processing between cognition and affection which results in physical movement in the form of behavior. For this reason, psychomotor skills are very crucial abilities to develop, especially in early childhood students. One of the uses of this development is to hone the gross motor and fine motor skills of young children. The results of monitoring the child's psychomotor development achievements can be used as a benchmark for meeting the child's own needs in facing education at the next level. This research aims to improve the psychomotor skills of young children through the implementation of Mandar culture-based Educational Game Tools (APE). The type of research used is classroom action research with a qualitative approach. Data collection was carried out through test techniques, observation interviews and documentation. The results of this research indicate that through the use of Mandar culture-based APE, the psychomotor abilities of early childhood children at Kumala KB Kindergarten can be improved both in terms of teacher teaching activities, children's learning activities, and test results, where in cycle I the psychomotor abilities of early childhood children were in the sufficient category and in cycle II the child's psychomotor abilities were in the good category.